2006
DOI: 10.1021/np0600402
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Triterpenoids from Salvia Species

Abstract: Salvia species are important medicinal and culinary plants, and they have been the subject of numerous chemical and biological studies. The bioactive triterpenoids of Salvia species, reported in the literature to date, are reviewed. About 200 triterpenoids, almost 80 of which are new, isolated, and characterized from about 100 Salvia species, are presented herein. In addition to the diverse biological activities of the pure triterpenoids, studies on biological activity of extracts of Salvia species are also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(122 citation statements)
references
References 128 publications
(165 reference statements)
1
101
0
12
Order By: Relevance
“…Two of these beverages (Samples 1 and 3) contain Anthraquinones, which possess a variety of antimicrobial, antioxidant, anti-inflammatory, antiviral, or antitumor promoting biological activities [31,32]. The presence of triterpenoids in three beverages precisely Samples 1-3 suggests the potential of the beverages exhibiting protective effects against cardiovascular disease and inflammation that are associated with this compound [33]. The intake level of the phytochemicals in the present study is low when compared with intake level of polyphenols of about 1 g in Europe [34].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these beverages (Samples 1 and 3) contain Anthraquinones, which possess a variety of antimicrobial, antioxidant, anti-inflammatory, antiviral, or antitumor promoting biological activities [31,32]. The presence of triterpenoids in three beverages precisely Samples 1-3 suggests the potential of the beverages exhibiting protective effects against cardiovascular disease and inflammation that are associated with this compound [33]. The intake level of the phytochemicals in the present study is low when compared with intake level of polyphenols of about 1 g in Europe [34].…”
Section: Discussionmentioning
confidence: 99%
“…Sage contains also important bioactive terpenoids such as triterpenoid ursolic and oleanolic acids [12] characterized by high lipophilicity [13]. Both components manifested hepatoprotective, anti-inflammatory, antihyperlipidemic and antitumorigenic properties [13].…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 99%
“…1) Several investigations showed that the chemical constituents of Salvia species were rich in triterpenoids, diterpenoids, monoterpenes and polyphenolics. [2][3][4][5] However, further chemical studies on the aerial parts of Salvia chinensis were left uncharacterized. In the course of our chemical studies on this plant, two new germacrane sesquiterpenes, salviadienol A (1) and salviadienol B (2), together with five known compounds (3)(4)(5)(6)(7) were isolated from the 70% ethanol extract of the aerial parts of Salvia chinensis.…”
Section: Notesmentioning
confidence: 99%